2014
DOI: 10.1155/2014/526932
|View full text |Cite
|
Sign up to set email alerts
|

P-Cresyl Sulfate Is a Valuable Predictor of Clinical Outcomes in Pre-ESRD Patients

Abstract: Background/Aims. Previous studies have reported p-cresyl sulfate (PCS) was related to endothelial dysfunction and adverse clinical effect. We investigate the adverse effects of PCS on clinical outcomes in a chronic kidney disease (CKD) cohort study. Methods. 72 predialysis patients were enrolled from a single medical center. Serum biochemistry data and PCS were measured. The clinical outcomes including cardiovascular event, all-cause mortality, and dialysis event were recorded during a 3-year follow-up. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
(36 reference statements)
0
30
0
Order By: Relevance
“…Other non-RCTs also reported that probiotics could change urinary p-cresol excretion and fecal p-cresol composition to some extent [28,29]. A 3-year longitudinal study indicated that a 5μmol/L increase of PCS might be associated with a 17% increased risk of rapid progression to dialysis in pre-dialysis CKD patients [30]. Another study with a larger sample size also supported the positive relationship of PCS and independent cardiovascular events [31].…”
Section: Discussionmentioning
confidence: 89%
“…Other non-RCTs also reported that probiotics could change urinary p-cresol excretion and fecal p-cresol composition to some extent [28,29]. A 3-year longitudinal study indicated that a 5μmol/L increase of PCS might be associated with a 17% increased risk of rapid progression to dialysis in pre-dialysis CKD patients [30]. Another study with a larger sample size also supported the positive relationship of PCS and independent cardiovascular events [31].…”
Section: Discussionmentioning
confidence: 89%
“…Although causal relationships between PCS and clinical outcomes are yet to be established, a 3-year longitudinal study in 74 predialysis patients showed that each 5-mmol/L increase in serum PCS was associated with a 12% (95% CI, 1% to 21%) increased risk of a cardiovascular event and a 17% (95% CI, 5% to 30%) increased risk of progressing to dialysis after controlling for eGFR and age (21). These results were supported in a larger cohort (n=499), which showed that free serum PCS was associated with cardiovascular events independent of both eGFR and Framingham risk factors (hazard ratio, 1.39; 95% CI, 1.02 to 1.89) (22).…”
Section: Discussionmentioning
confidence: 99%
“…PCS is a newly identified uremic toxin which has been associated with CKD progression and with cardiovascular disease and mortality risk (Wu et al, ; Lin et al, ; Lin et al, ; Lin et al, ). In the vasculature, PCS has been demonstrated to induce an inflammatory process, mainly by increasing ROS production in endothelial cells and leukocytes (Schepers et al, ; Itoh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…All available clinical studies on PCS, whether in hemodialysis or in CKD patients not yet on dialysis therapy, reported a strong association with cardiovascular mortality as well as with vascular disease (Wu et al, ; Lin et al, ; Lin et al, ; Lin et al, ).…”
mentioning
confidence: 99%